DIGITAL TECHNOLOGIES AND MODERN EDUCATION (Scientific Conference on Multidisciplinary Studies, 2025)
In recent years, the development of artificial intelligence (AI) technologies has led to significant changes in the field of education. AI provides opportunities for personalized learning, creating interactive educational materials, automating assessment systems, and supporting teachers. Machine learning, big data analysis, and natural language processing technologies play a crucial role in making the educational process more efficient and flexible. Artificial intelligence helps teachers track students' progress and provide individual assistance, while also offering students the ability to manage their learning process more effectively. This article analyzes how AI technologies have impacted the education system and how they have transformed teaching methods.